Ret mouse very large tumors (VLTs) display altered ratios of infiltrating memory to naive T cells: roles in tumor expansion - Khan, Mohammad Wasim Kayyum; Umansky, Viktor (Pathophysiology, 2016)
Melanoma is an aggressive skin cancer, however it is immunogenic. The size of the primary tumor is associated with the nodal metastases. Our goals were to characterize melanoma-associated antigens (MAAs) and tumor-infiltrating T-lymphocytes (TILs) subsets in the few very large tumors (VLTs) developing in ret transgenic mice of melanoma. Tumors >700mg (VLTs) were investigated for MAAs and subsets of TILs. Immunohistochemistry and flow cytometry-based studies were performed to determine the infiltration patterns of T-lymphocytes in VLTs. It was observed that zinc fixative restores the antigenicity of the cell-surface markers of lymphocyte subpopulations without the need of antigen retrieval, whereas formalin-based fixative fails to restore the antigenicity in the presence of antigen retrieval in the immunohistochemistry. VLTs from ret mice express MAAs, such as Tyrosinase, TRP-1, TRP-2 and gp-100. The mean±standard deviation (S.D.) T-cell infiltration per 400 times-high power field in VLTs; CD4+ (2.33±1.3), CD8+ (2.00±1.0), and CD4+ Foxp3+ (2.5±0.5) regulatory T cells infiltration was exclusively restricted to the tumor stroma. Moreover, our flow cytometry-based data reveal that % mean±S.D. naive CD3+ CD4+ T cell infiltration (32.8±4.0%) was significantly larger than effector (25.8±2.8%, p<0.01) and central memory cells (16.1±3.7%, p<0.001) in VLTs. Similarly, between CD3+ CD8+ T cells, naive cells infiltrate (57.7±2.3%) in a significantly larger frequency than effector (5.0±0.4%, p<0.0001) and central memory cell (4.8±1.7%, p<0.0001) subsets. These results suggest that the VLTs from ret mice display lowered infiltration ratios between memory and naive T cells, which could be associated with the relatively large growth of VLTs.